1970
DOI: 10.1172/jci106243
|View full text |Cite
|
Sign up to set email alerts
|

Long-term decay of serum cholesterol radioactivity: body cholesterol metabolism in normals and in patients with hyperlipoproteinemia and atherosclerosis

Abstract: A B S T R A C T After the intravenous injection of labeled cholesterol, the decay of specific radioactivity of total serum cholesterol was studied in 12 patients for 15-63 wk (average, 45 wk). In some, but not all of the patients studied, the slow slope of the decay curves suggested a deviation from monoexponential behavior, and the data of the slow period of the decay of specific activity were curve fitted by two exponentials. Six patients had serum lipid values regarded as normal and six had hyperlipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…The data were, accordingly, analyzed by "input-output analysis" (3,5), which is independent of the number of exponentials, but which limits the amount of information which can be derived from the data as compared with that obtainable by multicompartmental analysis. We believe that there are significant differences between the methods of curve fitting and data analysis employed by Samuel and Lieberman and by ourselves, and that these differences could in part account for the finding of a two-exponential, rather than a three-exponential fit in five patients by these investigators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were, accordingly, analyzed by "input-output analysis" (3,5), which is independent of the number of exponentials, but which limits the amount of information which can be derived from the data as compared with that obtainable by multicompartmental analysis. We believe that there are significant differences between the methods of curve fitting and data analysis employed by Samuel and Lieberman and by ourselves, and that these differences could in part account for the finding of a two-exponential, rather than a three-exponential fit in five patients by these investigators.…”
Section: Discussionmentioning
confidence: 99%
“…In 1968 two of us reported (1) that the plasma cholesterol specific radioactivity-time curves obtained in experiments of about 10 wk duration could be resolved into two exponential functions and, hence, that the turnover of plasma cholesterol conformed to a simple two-pool model. In 1970, Samuel and Perl (5) reported that in The Journal of Clinical Investigation Volume 57 January 1976-137-148 some patients the slow slope of the plasma decay curve deviated from monoexponential behavior after approximately 20-25 wk. This suggested that a multicompartmental model of more than two pools was necessary to describe the long-term turnover of plasma cholesterol in man.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the cholesterol content of extrahepatic tissues, measured directly in biopsies (13,14) or indirectly by isotope dilution analysis (15)(16)(17), has been only weakly correlated with the plasma total and LDL cholesterol concentrations. On the other hand, a recent study of hyperlipidemic subjects established that body cholesterol pool size shows a strong negative correlation with the plasma high density lipoprotein (HDL) concentration (17).…”
Section: Introductionmentioning
confidence: 99%
“…It is the purpose of this study to extend these findings to man with regard to the following parameters of adipocyte cholesterol: subcellular localization and degree of esterification; effects of cell number, cell size, and plasma cholesterol on adipocyte cholesterol concentration; in vitro cholesterol biosynthetic rates from radioactive glucose and acetate; and compartmental analysis of in vivo adipocyte cholesterol turnover after intravenous infusion of radioactive cholesterol. The last procedure requires the sum of a threeexponential equation to adequately describe cholesterol turnover in man (6,7). By fitting such an equation to both plasma and adipocyte specific activity curves simultaneously, it is possible to compare different threepool models (mammillary and catenary, Fig.…”
mentioning
confidence: 99%